PENGARUH PHYSICAL EVIDENCE, KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN DI LAWSON CABANG SERPONG - Widya, Rahmawati; Wijaya, Shierli (Jurnal Nusa Manajemen, 2024)
The purpose of this study was to determine whether there is an influence of physical evidence, product quality and promotion on purchasing decisions at Lawson, Serpong branch, Tangerang. The population in this study were consumers of Lawson, Serpong branch, Tangerang. The sample taken in this study was 390 respondents. By using quantitative methods. The sampling technique used is nonprobability sampling, namely the purposive sampling method. Data collection is done through a google form in the form of a questionnaire consisting of 5 Likert scale levels. The data analysis technique used in this study using SPSS 26. The results of this study indicate that the variables Physical Evidence, Product Quality and Promotion have a positive influence both partially and simultaneously on Purchasing Decisions at Lawson Serpong branch with a significant value <0.05. So it can be concluded that the alternative hypothesis (Ha) is accepted, which means that simultaneously all Physical Evidence, Product Quality, and Promotion variables have a significant effect on Purchasing Decisions at Lawson, Serpong branch..